Bioteknologi asas /disunting oleh John Bu'lock, Bjorn Kristiansen ; diterjemahkan oleh Yusuf Abdul Hamid, Ibrahim Che Omar, Darah Ibrahim - Bu'Lock, J. D. (John Desmond); Kristiansen, Bjorn; Yusuf Abdul Hamid; Ibrahim Che Omar; Darah Ibrahim (Pulau Pinang : Penerbit Universiti Sains Malaysia, 2002)
53